Preparation method of asymmetric quasi-solid electrolyte for enhancing interface stability
By using PVDF-HFP and P (VDF-TrFE-CFE) as the substrate polymer electrolyte and introducing BST and TiN nanofibers to construct a double-layer asymmetric structure solid electrolyte, the problems of low ionic conductivity and poor interface stability of polymer solid electrolyte are solved, and the effects of high ionic conductivity, wide electrochemical window and long cycle life are achieved.
Patent Information
- Application Number
- CN202510041587.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-10
AI Technical Summary
Polymer solid electrolytes have problems such as low ionic conductivity, poor interface stability, narrow electrochemical windows and short cycle life.
PVDF-HFP and P (VDF-TrFE-CFE) are used as polymer substrates, and solid electrolyte with a bilayer asymmetric structure is constructed by introducing barium strontium titanate (BST) nanofibers and titanium nitride (TiN) nanofibers to enhance interface stability.
It significantly improves the ion conductivity, lithium ion migration number and electrochemical window width of the electrolyte, and extends the cycle stability and service life of the battery.
Smart Images

Figure CN119833735A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a quasi-solid electrolyte. Background Art
[0002] The development of electric vehicles, grid energy storage and consumer electronics industries has deepened the global demand for lithium metal batteries with high energy density and long cycle life. Lithium metal batteries have become the next major research direction of lithium-ion batteries due to their higher theoretical specific capacity (3860mAh / g) and low redox potential (-3.04V vs standard hydrogen electrode). However, it is difficult for electrolytes and diaphragms to inhibit the growth of lithium dendrites. Dendrites piercing the diaphragm and short-circuiting the battery will cause severe thermal runaway or even explosion, posing huge safety hazards, which hinders the practical application of lithium metal batteries. As a link between the cathode and the lithium metal anode, solid electrolytes (SSEs) have the characteristics of being solvent-free and having high mechanical strength, and are expected to become an ideal substitute for liquid electrolytes.
[0003] Compared with inorganic solid electrolytes, polymer electrolytes have attracted much attention due to their excellent flexibility and film processing properties. If a solid-liquid hybrid system is used, the interfacial contact between the electrolyte and the electrode can be further improved, the interfacial impedance can be reduced, and thus the battery performance can be improved. However, polymer electrolytes still face the following challenges: (1) Insufficient mechanical strength makes it difficult to completely suppress the penetration of lithium dendrites; (2) Low ionic conductivity, especially at room temperature compared with liquid electrolytes; (3) Limited electrochemical window, easy to decompose under high pressure conditions, resulting in a decrease in electrochemical performance. These problems limit the application potential of polymer electrolytes in high-performance batteries.
[0004] At present, polymer materials such as polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF) and vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) have been widely used as the substrate of polymer electrolytes. However, existing polymer solid electrolytes have problems such as low ionic conductivity, poor interface stability, narrow electrochemical window and short cycle life. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of low ionic conductivity, poor interface stability, narrow electrochemical window and short cycle life of polymer solid electrolytes, and to provide a method for preparing an asymmetric quasi-solid electrolyte with enhanced interface stability.
[0006] A method for preparing an asymmetric quasi-solid electrolyte with enhanced interface stability is specifically completed by the following steps:
[0007] 1. Preparation of TiN nanofibers:
[0008] ①, dissolve polyvinyl pyrrolidone in a mixed solution of anhydrous ethanol and glacial acetic acid, stir magnetically until polyvinyl pyrrolidone is completely dissolved, then add tetrabutyl titanate and continue stirring until a uniform solution is formed, thereby obtaining electrospinning precursor solution I;
[0009] ②, transferring the electrospinning precursor solution I into a syringe, and then installing the syringe in an electrospinning machine for electrospinning. After the electrospinning is completed, the obtained fiber is placed in an air atmosphere, heated to 500°C to 600°C, and calcined for a period of time under the conditions of air atmosphere and 500°C to 600°C to obtain TiO2 nanofibers; the TiO2 nanofibers are placed in a tubular furnace, a mixed gas of ammonia / argon is introduced into the tubular furnace, the tubular furnace is heated to 900°C to 1000°C, and calcined for a period of time under the conditions of ammonia / argon mixed atmosphere and temperature of 900°C to 1000°C to obtain TiN nanofibers;
[0010] 2. Preparation of barium strontium titanate nanofibers:
[0011] ①, dissolve polyvinyl pyrrolidone, barium acetate and strontium acetate in a mixed solution of anhydrous ethanol and glacial acetic acid, stir magnetically until polyvinyl pyrrolidone is completely dissolved, then add tetrabutyl titanate and continue stirring until a uniform solution is formed, thereby obtaining electrospinning precursor solution II;
[0012] ②, transferring the electrospinning precursor solution II into a syringe, and then installing the syringe in an electrospinning machine for electrospinning. After the electrospinning is completed, the obtained fiber is placed in the air, heated to 800°C to 1000°C, and calcined for a period of time in an air atmosphere at a temperature of 800°C to 1000°C to obtain barium strontium titanate nanofibers;
[0013] 3. Preparation of pouring liquid:
[0014] ①, under ultrasonic conditions, disperse barium strontium titanate nanofibers in N,N-dimethylformamide, then add P(VDF-TrFE-CFE), PVDF-HFP and LiFSI, ultrasonicate and magnetically stir for a period of time to obtain casting liquid A;
[0015] ②, under ultrasonic conditions, TiN nanofibers were dispersed in N,N-dimethylformamide, and then P(VDF-TrFE-CFE), PVDF-HFP and LiFSI were added, and ultrasonic and magnetic stirring were performed for a period of time to obtain casting liquid B;
[0016] 4. Preparation of solid electrolyte:
[0017] ①. Place the casting liquid A in a vacuum condition to degas for a period of time, then cast it on a clean glass plate, scrape it into a film with a scraper, and then place it in a blast drying oven to dry for a period of time to obtain a BST layer;
[0018] ②. Pour casting liquid B on the BST layer, use a scraper to scrape it into a film, and then place it in a forced air drying oven to dry for a period of time to obtain a TiN-BST double-layer asymmetric solid electrolyte, that is, an asymmetric quasi-solid electrolyte with enhanced interface stability.
[0019] Principles and advantages of the present invention:
[0020] 1. The present invention uses PVDF-HFP and P(VDF-TrFE-CFE) as polymer substrates, wherein PVDF-HFP shows significant advantages due to its excellent heat resistance and good mechanical strength; and poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) (P(VDF-TrFE-CFE)) is more conducive to the dissociation of lithium salts due to its higher dielectric constant, thereby achieving higher room temperature ionic conductivity; mixing these two materials as a polymer matrix can not only take into account high mechanical strength and high ionic conductivity, but also is conducive to the manufacture of polymer electrolytes with high mechanical strength and high ionic conductivity, and the construction of high-performance lithium metal batteries;
[0021] Second, the present invention introduces barium strontium titanate (BST) nanofibers and titanium nitride (TiN) nanofibers to modify the polymer, thereby reducing the crystallinity of the polymer and improving the mechanical properties of the electrolyte; a double-layer asymmetric solid electrolyte is prepared by tape casting, in which the BST layer faces the positive electrode and the TiN layer faces the lithium metal negative electrode; the BST layer has a higher dielectric constant, which helps to promote the dissociation of lithium salts in the electrolyte, significantly improves the ionic conductivity of the electrolyte, and widens the electrochemical window; and the TiN layer can effectively inhibit the side reaction between the electrolyte membrane and lithium metal, further improving the cycle stability of the battery. The electrochemical performance test shows that the asymmetric quasi-solid electrolyte with enhanced interface stability prepared by the present invention has a high conductivity of up to 7.3×10 -4 The ionic conductivity is 0.034 S / cm, the lithium ion migration number is 0.74, and the electrochemical window is as wide as 4.8V. The LiFePO4||CSE||Li full battery assembled based on the electrolyte exhibits an initial discharge specific capacity of 140mAh / g at a rate of 1C, and the capacity retention rate is still over 75% after 1000 cycles. This indicates that the asymmetric quasi-solid electrolyte with enhanced interface stability provided by the present invention exhibits excellent performance in terms of cycle stability and service life, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1are electron microscope images and optical photographs; in the figure, (a) is a surface electron microscope image of the TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1, (b) is a cross-sectional electron microscope image of the TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1, (c) is an optical photograph of the TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1, (d) is a surface electron microscope image of the BST single-layer solid electrolyte prepared in Control Example 1, (e) is a cross-sectional electron microscope image of the BST single-layer solid electrolyte prepared in Control Example 1, (f) is an optical photograph of the BST single-layer solid electrolyte prepared in Control Example 1, (g) is a surface electron microscope image of the polymer solid electrolyte prepared in Control Example 2, (h) is a cross-sectional electron microscope image of the polymer solid electrolyte prepared in Control Example 2, and (i) is an optical photograph of the polymer solid electrolyte prepared in Control Example 2;
[0023] Figure 2 XRD patterns of the TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1, the BST single-layer solid electrolyte prepared in Comparative Example 1, and the polymer solid electrolyte prepared in Comparative Example 2;
[0024] Figure 3 The ionic conductivity of the TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1, the BST single-layer solid electrolyte prepared in Comparative Example 1, and the polymer solid electrolyte prepared in Comparative Example 2, and the lithium ion migration number of the lithium symmetric battery assembled using the same;
[0025] Figure 4 The electrochemical stability windows of the TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1, the BST single-layer solid electrolyte prepared in Comparative Example 1, and the polymer solid electrolyte prepared in Comparative Example 2;
[0026] Figure 5 The limiting current density of a lithium symmetric battery assembled using the TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1, the BST single-layer solid electrolyte prepared in Comparative Example 1, and the polymer solid electrolyte prepared in Comparative Example 2;
[0027] Figure 6 The rate performance curve of a LiFePO4||CSE||Li full battery assembled using the TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1, the BST single-layer solid electrolyte prepared in Control Example 1, and the polymer solid electrolyte prepared in Control Example 2;
[0028] Figure 7It is a cycle performance curve of a LiFePO4||CSE||Li full battery assembled using the TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1, the BST single-layer solid electrolyte prepared in Control Example 1, and the polymer solid electrolyte prepared in Control Example 2 at a 1C rate. DETAILED DESCRIPTION
[0029] Specific implementation method 1: This implementation method is a method for preparing an asymmetric quasi-solid electrolyte with enhanced interface stability, which is specifically completed according to the following steps:
[0030] 1. Preparation of TiN nanofibers:
[0031] ①, dissolve polyvinyl pyrrolidone in a mixed solution of anhydrous ethanol and glacial acetic acid, stir magnetically until polyvinyl pyrrolidone is completely dissolved, then add tetrabutyl titanate and continue stirring until a uniform solution is formed, thereby obtaining electrospinning precursor solution I;
[0032] ②, transferring the electrospinning precursor solution I into a syringe, and then installing the syringe in an electrospinning machine for electrospinning. After the electrospinning is completed, the obtained fiber is placed in an air atmosphere, heated to 500°C to 600°C, and calcined for a period of time under the conditions of air atmosphere and 500°C to 600°C to obtain TiO2 nanofibers; the TiO2 nanofibers are placed in a tubular furnace, a mixed gas of ammonia / argon is introduced into the tubular furnace, the tubular furnace is heated to 900°C to 1000°C, and calcined for a period of time under the conditions of ammonia / argon mixed atmosphere and temperature of 900°C to 1000°C to obtain TiN nanofibers;
[0033] 2. Preparation of barium strontium titanate nanofibers:
[0034] ①, dissolve polyvinyl pyrrolidone, barium acetate and strontium acetate in a mixed solution of anhydrous ethanol and glacial acetic acid, stir magnetically until polyvinyl pyrrolidone is completely dissolved, then add tetrabutyl titanate and continue stirring until a uniform solution is formed, thereby obtaining electrospinning precursor solution II;
[0035] ②, transferring the electrospinning precursor solution II into a syringe, and then installing the syringe in an electrospinning machine for electrospinning. After the electrospinning is completed, the obtained fiber is placed in the air, heated to 800°C to 1000°C, and calcined for a period of time in an air atmosphere at a temperature of 800°C to 1000°C to obtain barium strontium titanate nanofibers;
[0036] 3. Preparation of pouring liquid:
[0037] ①, under ultrasonic conditions, disperse barium strontium titanate nanofibers in N,N-dimethylformamide, then add P(VDF-TrFE-CFE), PVDF-HFP and LiFSI, ultrasonicate and magnetically stir for a period of time to obtain casting liquid A;
[0038] ②, under ultrasonic conditions, TiN nanofibers were dispersed in N,N-dimethylformamide, and then P(VDF-TrFE-CFE), PVDF-HFP and LiFSI were added, and ultrasonic and magnetic stirring were performed for a period of time to obtain casting liquid B;
[0039] 4. Preparation of solid electrolyte:
[0040] ①. Place the casting liquid A in a vacuum condition to degas for a period of time, then cast it on a clean glass plate, scrape it into a film with a scraper, and then place it in a blast drying oven to dry for a period of time to obtain a BST layer;
[0041] ②. Pour casting liquid B on the BST layer, use a scraper to scrape it into a film, and then place it in a forced air drying oven to dry for a period of time to obtain a TiN-BST double-layer asymmetric solid electrolyte, that is, an asymmetric quasi-solid electrolyte with enhanced interface stability.
[0042] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that the volume ratio of the mass of polyvinyl pyrrolidone described in step 1① to the mixed solution of anhydrous ethanol and glacial acetic acid is (1.5g-2.5g):(10mL-20mL); the volume ratio of anhydrous ethanol to glacial acetic acid in the mixed solution of anhydrous ethanol and glacial acetic acid described in step 1① is 1:1; the volume ratio of tetrabutyl titanate to the mixed solution of anhydrous ethanol and glacial acetic acid described in step 1① is (4mL-5mL):(10mL-20mL). The other steps are the same as those in specific implementation method 1.
[0043] Specific embodiment 3: The difference between this embodiment and specific embodiment 1 or 2 is that: the process parameters of the electrospinning described in step 1 ② are: using a 20-gauge needle, a liquid supply rate of 1.5 mL / h to 2 mL / h, a voltage of 25 kV to 30 kV, and a distance between the needle and the electrode plate of 12 cm to 18 cm; in step 1 ②, the obtained fiber is placed in an air atmosphere, heated to 500°C to 600°C at a heating rate of 1°C / min to 2°C / min, and calcined for 3h to 4h in an air atmosphere at 500°C to 600°C. The other steps are the same as those in specific embodiment 1 or 2.
[0044] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the volume ratio of ammonia to argon in the ammonia / argon mixed gas described in step 1 ② is 1:1; in step 1 ②, the ammonia / argon mixed gas is introduced into the tubular furnace, the tubular furnace is heated to 900°C to 1000°C at a heating rate of 5°C / min to 10°C / min, and calcined for 2h to 3h in the ammonia / argon mixed atmosphere and a temperature of 900°C to 1000°C. The other steps are the same as those of specific embodiments 1 to 3.
[0045] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the mass ratio of polyvinyl pyrrolidone, barium acetate and strontium acetate described in step 2① is (0.5g~0.7g):(2g~3g):(0.4g~0.5g); the volume ratio of the mass of polyvinyl pyrrolidone described in step 2① to the mixed solution of anhydrous ethanol and glacial acetic acid is (0.5g~0.7g):(8mL~15mL); the volume ratio of the mass of polyvinyl pyrrolidone described in step 2① to tetrabutyl titanate is (0.5g~0.7g):(3mL~3.5mL); the volume ratio of anhydrous ethanol to glacial acetic acid in the mixed solution of anhydrous ethanol and glacial acetic acid described in step 2① is 1:1. The other steps are the same as specific embodiments 1 to 4.
[0046] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that: the process parameters of the electrospinning described in step 2② are: using a 20-gauge needle, a liquid supply rate of 1.5mL / h to 2mL / h, a voltage of 18kV to 25kV, and a distance between the needle and the electrode plate of 12cm to 18cm; in step 2②, the obtained fiber is placed in air, heated to 800℃ to 1000℃ at a heating rate of 5℃ / min to 10℃ / min, and calcined for 4h to 6h in an air atmosphere at a temperature of 800℃ to 1000℃. The other steps are the same as those of specific embodiments 1 to 5.
[0047] Specific embodiment 7: The difference between this embodiment and specific embodiments 1 to 6 is that: the mass ratio of the barium strontium titanate nanofiber described in step 3① to the volume ratio of N,N-dimethylformamide is (50mg~60mg):(3mL~4mL); the mass ratio of P(VDF-TrFE-CFE), PVDF-HFP and LiFSI described in step 3① is (0.1g~0.2g):(0.1g~0.2g):(0.1g~0.3g); the mass ratio of the barium strontium titanate nanofiber described in step 3① to P(VDF-TrFE-CFE) is (50mg~60mg):(0.1g~0.2g); the time of ultrasonic and magnetic stirring in step 3① is 10h~12h. The other steps are the same as specific embodiments 1 to 6.
[0048] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the mass ratio of the TiN nanofiber described in step three ② to the volume ratio of N,N-dimethylformamide is (25mg-30mg): (3mL-4mL); the mass ratio of P(VDF-TrFE-CFE), PVDF-HFP and LiFSI described in step three ② is (0.1g-0.2g): (0.1g-0.2g): (0.1g-0.3g); the mass ratio of the TiN nanofiber described in step three ② to P(VDF-TrFE-CFE) is (25mg-30mg): (0.1g-0.2g); the time of ultrasonic and magnetic stirring in step three ② is 10h-12h. The other steps are the same as specific embodiments one to seven.
[0049] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the degassing time in step 4① is 20min to 40min; in step 4①, a 500μm scraper is used to scrape the film, and then the film is placed in a blast drying oven at a temperature of 50℃ to 60℃ for 2h to 3h to obtain a BST layer. The other steps are the same as those in specific embodiments 1 to 8.
[0050] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: in step 4②, a 500 μm scraper is used to scrape the film, and then the film is placed in a blast drying oven at a temperature of 50°C to 60°C for 10h to 14h to obtain a TiN-BST double-layer asymmetric solid electrolyte. The other steps are the same as those of specific embodiments 1 to 9.
[0051] The following examples are used to verify the beneficial effects of the present invention:
[0052] Example 1: A method for preparing an asymmetric quasi-solid electrolyte with enhanced interface stability is specifically completed by the following steps:
[0053] 1. Preparation of TiN nanofibers:
[0054] ① Dissolve 2 g of polyvinyl pyrrolidone in a mixed solution of 7 mL of anhydrous ethanol and 7 mL of glacial acetic acid, stir magnetically until the polyvinyl pyrrolidone is completely dissolved, then add 4.5 mL of tetrabutyl titanate and continue stirring until a uniform solution is formed to obtain an electrospinning precursor solution I;
[0055] ②, transfer the electrospinning precursor solution I to a syringe, and then install the syringe in an electrospinning machine for electrospinning. After the electrospinning is completed, place the obtained fiber in an air atmosphere, heat it from room temperature to 550°C at a heating rate of 2°C / min, and then calcine it at 550°C in an air atmosphere for 3 hours to obtain TiO2 nanofibers; put the TiO2 nanofibers into a tubular furnace, introduce a mixed gas of ammonia / argon into the tubular furnace, heat the tubular furnace from room temperature to 1000°C at a heating rate of 5°C / min, and calcine it at a temperature of 1000°C in a mixed atmosphere of ammonia / argon for 2 hours to obtain TiN nanofibers;
[0056] The process parameters of the electrospinning described in step 1② are: using a 20-gauge needle, a liquid supply rate of 1.5 mL / h, a voltage of 27 kV, and a distance of 15 cm between the needle and the electrode plate;
[0057] The volume ratio of ammonia to argon in the ammonia / argon mixed gas described in step 1② is 1:1;
[0058] 2. Preparation of barium strontium titanate nanofibers:
[0059] ①, dissolve 0.6g polyvinyl pyrrolidone, 2.043g barium acetate and 0.410g strontium acetate in a mixed solution of 5mL anhydrous ethanol and 5mL glacial acetic acid, stir magnetically until polyvinyl pyrrolidone is completely dissolved, then add 3.4mL tetrabutyl titanate and continue stirring until a uniform solution is formed to obtain electrospinning precursor solution II;
[0060] ②, transfer the electrospinning precursor solution II into a syringe, and then install the syringe in an electrospinning machine for electrospinning. After the electrospinning is completed, place the obtained fiber in air, heat it from room temperature to 800°C at a heating rate of 5°C / min, and calcine it in an air atmosphere at a temperature of 800°C for 4 hours to obtain barium strontium titanate nanofibers (BST nanofibers);
[0061] The process parameters of the electrospinning described in step 2② are: using a 20-gauge needle, a liquid supply rate of 1.5 / mLh, a voltage of 18 kV, and a distance of 15 cm between the needle and the electrode plate;
[0062] 3. Preparation of pouring liquid:
[0063] ①, under ultrasonic conditions, 56 mg of barium strontium titanate nanofibers were dispersed in 3 mL of N,N-dimethylformamide (DMF), and then 0.15 g of poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) (P(VDF-TrFE-CFE)), 0.15 g of vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) and 0.2 g of lithium bis(fluorosulfonyl)imide (LiFSI) were added, and ultrasonic and magnetic stirring were performed for 12 h to obtain casting liquid A;
[0064] ②, under ultrasonic conditions, 28 mg of TiN nanofibers were dispersed in 3 mL of N,N-dimethylformamide (DMF), and then 0.15 g of poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene), 0.15 g of vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) and 0.2 g of lithium bis(fluorosulfonyl)imide (LiFSI) were added, and ultrasonic and magnetic stirring were performed for 12 h to obtain casting liquid B;
[0065] 4. Preparation of solid electrolyte:
[0066] ①. Degas the casting liquid A under vacuum for 30 minutes, then cast it on a clean glass plate, scrape it into a film using a 500μm scraper, and then dry it in a blast drying oven at 55°C for 2 hours to obtain a BST layer;
[0067] ②. Pour casting liquid B on the BST layer, use a 500μm scraper to scrape it into a film, and then place it in a 55°C forced air drying oven to dry for 12 hours to obtain a TiN-BST double-layer asymmetric solid electrolyte, which is an asymmetric quasi-solid electrolyte with enhanced interface stability (denoted as TiN-BST).
[0068] Comparative Example 1: The preparation method of BST single-layer solid electrolyte is specifically completed according to the following steps:
[0069] ①, under ultrasonic conditions, 28 mg TiN nanofibers were dispersed in 3 mL N,N-dimethylformamide (DMF), and then 0.15 g poly (vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene), 0.15 g vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) and 0.2 g lithium bis(fluorosulfonyl)imide (LiFSI) were added, and ultrasonic and magnetic stirring were performed for 12 h to obtain casting liquid B;
[0070] ②. Degas the casting liquid B under vacuum conditions for 30 minutes, then cast it on a clean glass plate, use a 750μm scraper to scrape it into a film, and then place it in a 55°C forced air drying oven to dry for 12 hours to obtain a BST single-layer solid electrolyte (recorded as 10wt% BST).
[0071] Comparative Example 2: The preparation method of the polymer solid electrolyte is specifically completed according to the following steps:
[0072] ①, 0.15g poly (vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene), 0.15g vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) and 0.2g lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 3mL N,N-dimethylformamide (DMF), and ultrasonicated and magnetically stirred for 12h to obtain casting liquid C;
[0073] ②. Degas the casting liquid C under vacuum conditions for 30 minutes, then cast it on a clean glass plate, use a 750μm scraper to scrape it into a film, and then place it in a 55℃ forced air drying oven to dry for 12 hours to obtain a polymer solid electrolyte (referred to as Mixed polymer).
[0074] Figure 1 (a, d, g) respectively show the surface scanning electron microscope images of the TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1, the electrolyte doped with 10 wt% BST nanofibers (BST single-layer solid electrolyte) prepared in Control Example 1, and the polymer electrolyte (Mixed polymer) prepared in Control Example 2. It can be observed that the surface of the electrolyte membrane after doping with inorganic fillers is smoother, with only a small number of small pores formed by solvent volatilization during the drying process. Figure 1 (b, e, h) are cross-sectional electron micrographs of the electrolyte, showing that the film thickness is controlled between 40 and 50 μm, the internal structure is relatively dense, and there are fewer pores, which is conducive to the effective transmission of lithium ions inside. Among them, the TiN-BST film shows a clear layered structure, reflecting the successful preparation of the double-layer structure. Figure 1 (c, f, i) are optical photographs of TiN-BST double-layer asymmetric solid electrolyte, electrolyte doped with 10wt% BST nanofibers, and polymer electrolyte. The electrolyte membrane without filler has high transparency, while after doping with BST, the film is uniformly white. The TiN-BST double-layer electrolyte appears black and white on both sides, further verifying the successful preparation of the double-layer structure.
[0075] Figure 2 The XRD patterns of the three samples are shown. It can be observed that after doping with TiN and BST nanofibers, the characteristic peaks of the polymer crystallization become broader and the intensity weakens, indicating that its crystallization behavior is suppressed, which helps the rapid transmission of lithium ions in the electrolyte. In addition, in the spectrum, corresponding characteristic peaks appear at the positions corresponding to the standard crystal card PDF#06-0642 of TiN and the standard crystal card PDF#89-0274 of BST, which further confirms that TiN and BST nanofibers are successfully doped into the electrolyte membrane.
[0076] Figure 3The ionic conductivity and lithium ion migration number of three solid electrolytes were demonstrated. After being doped with BST nanofibers, the ionic conductivity and lithium ion migration number of the electrolyte were significantly improved, indicating that the high dielectric constant of BST effectively promoted the dissociation of lithium salts, and the introduction of nanofibers constructed a continuous lithium ion transmission path inside the electrolyte, thereby greatly enhancing the ion migration ability. Further using a TiN-BST double-layer electrolyte, the ionic conductivity was increased to 0.73mS / cm, and the migration number was also significantly increased to 0.74. The doping of surface TiN nanofibers improved the electrochemical properties of the quasi-solid electrolyte and further optimized the overall ion transport characteristics of the electrolyte.
[0077] Assembling a lithium symmetric cell:
[0078] The TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1 was cut into discs with a diameter of 14 mm and transferred to a glove box filled with argon. When assembling the battery, 2 μL of lithium electrolyte was dripped on both sides of the membrane to improve the interface contact between the electrode and the electrolyte; the electrolyte was a mixture of LiPF6 and FEC in EC, DEC and EMC, wherein the volume ratio of EC:DEC:EMC was 1:1:1, the concentration of LiPF6 in the electrolyte was 1 M, and the mass fraction of FEC was 5%;
[0079] The TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1 was assembled into a lithium symmetric battery, with lithium sheets with a diameter of 10 mm on both sides of the electrolyte as electrodes, and the battery was assembled in a glove box filled with argon;
[0080] According to the above method, the BST single-layer solid electrolyte prepared in Control Example 1 and the polymer solid electrolyte prepared in Control Example 2 were assembled into lithium symmetric batteries respectively.
[0081] like Figure 4 As shown in Figure 1, the electrochemical stability window of the quasi-solid electrolyte was tested by linear sweep voltammetry. The oxidation potential of the TiN-BST double-layer asymmetric solid electrolyte is 4.8V, which can meet the working requirements of the positive electrode material of lithium batteries. At the same time, the TiN-BST double-layer asymmetric solid electrolyte does not show an obvious reduction peak at 0V, indicating that it has good anti-reduction properties.
[0082] The limiting current density of the quasi-solid electrolyte was characterized by assembling lithium symmetric cells, e.g. Figure 5 As shown, the limiting current density of the undoped quasi-solid electrolyte is 0.45 mA / cm 2 After doping with BST nanofibers, the overpotential of the symmetric cell decreased, and the limiting current density increased to 0.65 mA / cm 2The TiN pair can better suppress lithium dendrites and further increase the limiting current density to 1.4 mA / cm 2 .
[0083] Figure 5 TiN-BST double-layer is a lithium symmetric battery assembled using the TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1; 10wt% BST is a lithium symmetric battery assembled using the BST single-layer solid electrolyte prepared in Control Example 1; Mixed polymer is a lithium symmetric battery assembled using the polymer solid electrolyte prepared in Control Example 2.
[0084] Assembling LiFePO4||CSE||Li full battery:
[0085] The TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1, the BST single-layer solid electrolyte prepared in Control Example 1, and the polymer solid electrolyte prepared in Control Example 2 were cut into discs with a diameter of 14 mm, and transferred to a glove box filled with argon. When assembling the battery, 2 μL of lithium battery electrolyte was dripped on both sides of the membrane to improve the interface contact between the electrode and the electrolyte; the electrolyte was a mixture of LiPF6 and FEC in EC, DEC and EMC, wherein the volume ratio of EC:DEC:EMC was 1:1:1, the concentration of LiPF6 in the electrolyte was 1 M, and the mass fraction of FEC was 5%;
[0086] The TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1 was assembled into a quasi-solid-state lithium metal battery, wherein the positive electrode was composed of lithium iron phosphate, superconducting carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10, the negative electrode was a metal lithium sheet with a diameter of 14 mm, and 4 μL of lithium hexafluorophosphate electrolyte was dripped on each side of the electrolyte. The battery was assembled in a glove box filled with argon.
[0087] According to the above method, the BST single-layer solid electrolyte prepared in Control Example 1 and the polymer solid electrolyte prepared in Control Example 2 are respectively assembled into a LiFePO4||CSE||Li full battery;
[0088] Figure 6 and Figure 7 TiN-BST double-layer is a LiFePO4||CSE||Li full battery assembled using the TiN-BST double-layer asymmetric solid electrolyte prepared in Example 1; 10wt% BST is a LiFePO4||CSE||Li full battery assembled using the BST single-layer solid electrolyte prepared in Control Example 1; Mixed polymer is a LiFePO4||CSE||Li full battery assembled using the polymer solid electrolyte prepared in Control Example 2.
[0089] Figure 6 The rate performance of the battery assembled by LiFePO4 positive electrode, quasi-solid electrolyte and lithium metal negative electrode was demonstrated. The unmodified quasi-solid electrolyte has a discharge capacity of 150mAh / g at a rate of 0.1C, but its discharge capacity decays rapidly with the increase of charge and discharge rate. When the rate increases to 5C and 10C, the discharge capacity is only 54mAh / g and 30mAh / g. After BST nanofiber doping modification, the quasi-solid electrolyte has higher ionic conductivity and lithium ion migration number, and its rate performance is improved. Due to the reduction of interfacial side reactions, the LiFePO4||CSE||Li full battery assembled with TiN-BST double-layer asymmetric solid electrolyte not only shows a high discharge capacity of 160mAh / g at a rate of 0.1C, but also has a specific capacity of 97mAh / g and 72mAh / g even when the rate is increased to 5C and 10C, and has the ability of fast charge and discharge, which fully proves that the modified quasi-solid electrolyte has excellent rate performance.
[0090] Figure 7 The cycling performance of the quasi-solid-state battery at 1C rate was demonstrated. The initial discharge capacity of the unmodified polymer electrolyte was about 124 mAh / g, and the capacity dropped rapidly after 100 cycles, and the capacity retention rate dropped to less than 50% after 200 cycles. The performance of the quasi-solid-state electrolyte modified with BST nanofibers was enhanced, with an initial discharge capacity of 135 mAh / g at 1C. However, due to poor interface stability, the capacity retention rate did not exceed 60% after 300 cycles. After adding the TiN functional layer, the LiFePO4||CSE||Li full battery assembled with the TiN-BST double-layer asymmetric solid electrolyte had a high initial discharge capacity (140 mAh / g) and still had a capacity of 107 mAh / g after 1000 cycles, with a capacity retention rate of more than 75%. This shows that after the doping modification of TiN nanofibers, the electrochemical performance of the quasi-solid-state electrolyte is effectively improved, and the assembled battery has excellent cycling performance and discharge capacity.
Claims
1. A method for preparing an asymmetric quasi-solid electrolyte with enhanced interface stability, characterized in that The preparation method is specifically completed according to the following steps:
1. Preparation of TiN nanofibers: ①, dissolve polyvinyl pyrrolidone in a mixed solution of anhydrous ethanol and glacial acetic acid, stir magnetically until polyvinyl pyrrolidone is completely dissolved, then add tetrabutyl titanate and continue stirring until a uniform solution is formed, thereby obtaining electrospinning precursor solution I; ②, transferring the electrospinning precursor solution I into a syringe, and then installing the syringe in an electrospinning machine for electrospinning. After the electrospinning is completed, the obtained fiber is placed in an air atmosphere, heated to 500°C to 600°C, and calcined for a period of time under the conditions of air atmosphere and 500°C to 600°C to obtain TiO2 nanofibers; the TiO2 nanofibers are placed in a tubular furnace, a mixed gas of ammonia / argon is introduced into the tubular furnace, the tubular furnace is heated to 900°C to 1000°C, and calcined for a period of time under the conditions of ammonia / argon mixed atmosphere and a temperature of 900°C to 1000°C to obtain TiN nanofibers; 2. Preparation of barium strontium titanate nanofibers: ①, dissolve polyvinyl pyrrolidone, barium acetate and strontium acetate in a mixed solution of anhydrous ethanol and glacial acetic acid, stir magnetically until polyvinyl pyrrolidone is completely dissolved, then add tetrabutyl titanate and continue stirring until a uniform solution is formed, thereby obtaining electrospinning precursor solution II; ②, transferring the electrospinning precursor solution II into a syringe, and then installing the syringe in an electrospinning machine for electrospinning. After the electrospinning is completed, the obtained fiber is placed in the air, heated to 800°C to 1000°C, and calcined for a period of time in an air atmosphere at a temperature of 800°C to 1000°C to obtain barium strontium titanate nanofibers; 3. Preparation of pouring liquid: ①, under ultrasonic conditions, disperse barium strontium titanate nanofibers in N,N-dimethylformamide, then add P(VDF-TrFE-CFE), PVDF-HFP and LiFSI, ultrasonicate and magnetically stir for a period of time to obtain casting liquid A; ②, under ultrasonic conditions, TiN nanofibers were dispersed in N,N-dimethylformamide, and then P(VDF-TrFE-CFE), PVDF-HFP and LiFSI were added, and ultrasonic and magnetic stirring were performed for a period of time to obtain casting liquid B; 4. Preparation of solid electrolyte: ①. Place the casting liquid A in a vacuum condition to degas for a period of time, then cast it on a clean glass plate, scrape it into a film with a scraper, and then place it in a blast drying oven to dry for a period of time to obtain a BST layer; ②. Pour casting liquid B on the BST layer, use a scraper to scrape it into a film, and then place it in a forced air drying oven to dry for a period of time to obtain a TiN-BST double-layer asymmetric solid electrolyte, which is an asymmetric quasi-solid electrolyte with enhanced interface stability.
2. The method for preparing an asymmetric quasi-solid electrolyte with enhanced interface stability according to claim 1, characterized in that The volume ratio of the mass of polyvinyl pyrrolidone described in step 1① to the mixed solution of anhydrous ethanol and glacial acetic acid is (1.5g~2.5g):(10mL~20mL); the volume ratio of anhydrous ethanol to glacial acetic acid in the mixed solution of anhydrous ethanol and glacial acetic acid described in step 1① is 1:1; the volume ratio of tetrabutyl titanate described in step 1① to the mixed solution of anhydrous ethanol and glacial acetic acid is (4mL~5mL):(10mL~20mL).
3. The method for preparing an asymmetric quasi-solid electrolyte with enhanced interface stability according to claim 1, characterized in that The process parameters of the electrospinning described in step 1② are: using a No. 20 needle, a liquid supply rate of 1.5mL / h~2mL / h, a voltage of 25kV~30kV, and a distance between the needle and the electrode plate of 12cm~18cm; in step 1②, the obtained fiber is placed in an air atmosphere, heated to 500℃~600℃ at a heating rate of 1℃ / min~2℃ / min, and calcined for 3h~4h in an air atmosphere and 500℃~600℃.
4. The method for preparing an asymmetric quasi-solid electrolyte with enhanced interface stability according to claim 1, characterized in that The volume ratio of ammonia to argon in the ammonia / argon mixed gas described in step 1② is 1:1; in step 1②, the ammonia / argon mixed gas is introduced into the tubular furnace, the tubular furnace is heated to 900℃~1000℃ at a heating rate of 5℃ / min~10℃ / min, and calcined for 2h~3h in the ammonia / argon mixed atmosphere and a temperature of 900℃~1000℃.
5. The method for preparing an asymmetric quasi-solid electrolyte with enhanced interface stability according to claim 1, characterized in that The mass ratio of polyvinyl pyrrolidone, barium acetate and strontium acetate described in step 2① is (0.5g~0.7g):(2g~3g):(0.4g~0.5g); the volume ratio of the mass of polyvinyl pyrrolidone described in step 2① to the mixed solution of anhydrous ethanol and glacial acetic acid is (0.5g~0.7g):(8mL~15mL); the volume ratio of the mass of polyvinyl pyrrolidone described in step 2① to tetrabutyl titanate is (0.5g~0.7g):(3mL~3.5mL); the volume ratio of anhydrous ethanol to glacial acetic acid in the mixed solution of anhydrous ethanol and glacial acetic acid described in step 2① is 1:
1.
6. The method for preparing an asymmetric quasi-solid electrolyte with enhanced interface stability according to claim 1, characterized in that The process parameters of the electrospinning described in step 2② are: using a No. 20 needle, a liquid supply rate of 1.5mL / h~2mL / h, a voltage of 18kV~25kV, and a distance between the needle and the electrode plate of 12cm~18cm; in step 2②, the obtained fiber is placed in the air, heated to 800℃~1000℃ at a heating rate of 5℃ / min~10℃ / min, and calcined in an air atmosphere and a temperature of 800℃~1000℃ for 4h~6h.
7. The method for preparing an asymmetric quasi-solid electrolyte with enhanced interface stability according to claim 1, characterized in that The mass ratio of the barium strontium titanate nanofibers described in step 3① to the volume ratio of N,N-dimethylformamide is (50mg~60mg):(3mL~4mL); the mass ratio of P(VDF-TrFE-CFE), PVDF-HFP and LiFSI described in step 3① is (0.1g~0.2g):(0.1g~0.2g):(0.1g~0.3g); the mass ratio of the barium strontium titanate nanofibers described in step 3① to P(VDF-TrFE-CFE) is (50mg~60mg):(0.1g~0.2g); the time of ultrasonic and magnetic stirring in step 3① is 10h~12h.
8. The method for preparing an asymmetric quasi-solid electrolyte with enhanced interface stability according to claim 1, characterized in that The mass ratio of the TiN nanofibers described in step 3② to the volume ratio of N,N-dimethylformamide is (25mg~30mg):(3mL~4mL); the mass ratio of P(VDF-TrFE-CFE), PVDF-HFP and LiFSI described in step 3② is (0.1g~0.2g):(0.1g~0.2g):(0.1g~0.3g); the mass ratio of the TiN nanofibers described in step 3② to P(VDF-TrFE-CFE) is (25mg~30mg):(0.1g~0.2g); the time for ultrasonic and magnetic stirring in step 3② is 10h~12h.
9. The method for preparing an asymmetric quasi-solid electrolyte with enhanced interface stability according to claim 1, characterized in that The degassing time in step 4① is 20min to 40min; in step 4①, a 500μm scraper is used to scrape it into a film, and then placed in a forced air drying oven at a temperature of 50℃ to 60℃ for 2h to 3h to obtain a BST layer.
10. The method for preparing an asymmetric quasi-solid electrolyte with enhanced interface stability according to claim 1, characterized in that In step 4②, a 500 μm scraper is used to scrape it into a film, and then placed in a forced air drying oven at a temperature of 50° C. to 60° C. to dry for 10 h to 14 h to obtain a TiN-BST double-layer asymmetric solid electrolyte.
Citation Information
Patent Citations
Preparation method and application of titanium nitride fiber reinforced quasi-solid electrolyte
CN116742111A
Fiber diaphragm, preparation method thereof and application of fiber diaphragm in in-situ polymerization solid-state lithium battery
CN117594951A
Functional fiber diaphragm, preparation method thereof and application of functional fiber diaphragm in polymer solid-state lithium battery
CN118315765A
Nanocomposite electrospun materials based on cu 2o / carbon as anodes for lithium batteries
WO2020104120A1